Age Determination of Young Rocks and Artifacts - Wagner, Günther A. author. aut Link
XVIII, 466 p.
Keywords: The Quaternary, which spans approximately the last 2 million years, is characterized by dramatic environmental changes, commonly known as the "ice age". During this period, man with his manifold cultures evolved. Attempts at dating these events as accurately as possible have made great progress. The broad spectrum of physical and chemical dating methods, now available for dating human artifacts and Quaternary rocks, is becoming increasingly difficult to grasp. In this book the various chronometric techniques are comprehensively and intelligibly treated. By means of numerous case studies, taken from archaeology and Quaternary geology, the potential and limitation of these techniques are demonstrated. The book is intended mainly for scientists and students of these fields, but the interested layman may also find its rewarding.